2011
DOI: 10.1155/2011/539356
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Composition, Antioxidant Activities, and Antiulcer Potential of Lentinus squarrosulus (Mont.) Mycelia Extract

Abstract: Water extract of Lentinus squarrosulus mycelia was analysed for nutritional content, antioxidant capacity, and antiulcer ability. The extract contains high protein (57.6 g/100 g) and low total fat (0.5 g/100 g) and is rich in magnesium (0.4 g/100 g), potassium (3.8 g/100 g), vitamins B1 (1.42 mg/100 g), and B3 (194.29 mg/100 g) with total phenolic content of 39.16 mg/100 g. The cupric reducing antioxidant capacity and 1,1-diphenyl-2-picrylhydrazyl radical scavenging activity of the extract were A450 of 0.20 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…are the most cultivated mushrooms worldwide (Chang, 1998). Other cultivated mushrooms include members of the genus Auricularia (Tang et al, 2010), Pleurotus (Cohen et al, 2002;Obodai et al, 2011;Royse, 1992) and, to a lesser extent, Lentinus (Adesina et al, 2011;Mhd Omar et al, 2011;Nwanze et al, 2006;Pukahuta et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…are the most cultivated mushrooms worldwide (Chang, 1998). Other cultivated mushrooms include members of the genus Auricularia (Tang et al, 2010), Pleurotus (Cohen et al, 2002;Obodai et al, 2011;Royse, 1992) and, to a lesser extent, Lentinus (Adesina et al, 2011;Mhd Omar et al, 2011;Nwanze et al, 2006;Pukahuta et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The mushroom is usually found in the wild on dead or decaying wood (Karunarathna et al, 2011) of various trees. It is widely known as an indigenous mushroom in Nigeria (Adesina et al, 2011;Nwanze et al, 2005), having been reported to have various organoleptic, nutritional and medicinal attributes (Mhd Omar et al, 2011;Nwanze et al, 2006). L. squarrosulus has been reported to be rich in proteins, sugars, lipids, amino acids, vitamins B, C, and D, and minerals (Mhd Omar et al, 2011;Royse et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations